Pengaruh Pengendalain Internal Terhadap Kualitas Laporan Keuangan Daerah - R. Deni Purana; Iwan Sidharta (Majalah Bisnis & IPTEK, 2018)
One of the goals to be produced from the use of information technology in the application of information systems is quality information. The purpose of this study is to investigate the effect of internal controls on the quality of regional financial statements in answering the hypothesis proposed by using a quantitative approach with simple linear regression analysis techniques. Verification is carried out with a sample of 30 employees at one of the regional government offices in the city of Bandung. Based on the results of data processing shows that there is a significant influence of internal control over the quality of regional financial statements. Thus it can be recommended for the parties concerned to improve internal control so that it can produce quality regional financial report information.